Magnetically enhancing diffusion for dendrite-free and long-term stable lithium metal anodes - Yongxiu Chen; Xiangyu Dou; Kai Wang; Yongsheng Han (Green Energy & Environment, 2022)
Lithium metal batteries are promising devices for the next-generation energy storage due to their ultrahigh theoretical specific capacity and extremely low electrochemical potential. Their inherent problem is the formation of lithium dendrites in cycling, which has induced safety concerns for almost half a century. After understanding the formation mechanism of branching structures, we propose to suppress lithium dendrites by adopting external magnetic fields to induce diffusion enhancement at the interface of the anode, thus attenuating concentration gradient there and reducing the driving force for the formation of dendritic structures. The diffusion coefficient of lithium ions is dependent on the strength of magnetic fields, confirming the effectiveness of magnetic fields in improving Li+ diffusion. After employing the magnetic field of 0.8 T, the concentration gradients at the growth front becomes nearly half of the control case, which leads to a dendrite-free lithium deposition up to the high current density of 10 mA cm−2. Both the Cu|LiCoO2 batteries and the symmetric Li|Li coin cells show a long-term stable cycling at high current densities under the assistance of magnetic field. This diffusion enhanced technique promises a facile and general approach to suppress dendritic structures in secondary batteries, which may help to develop quick charging strategies.